Naturally Occurring Animal Models of Human Hepatitis E Virus Infection - Yugo, Danielle M. (Oxford University Press, 2014)
Hepatitis E virus (HEV) is a single-stranded, positive-sense RNA virus in the family Hepeviridae. Hepatitis E caused by HEV is a clinically important global disease. There are currently four well-characterized genotypes of HEV in mammalian species, although numerous novel strains of HEV likely belonging to either new genotypes or species have recently been identified from several other animal species. HEV genotypes 1 and 2 are limited to infection in humans, whereas genotypes 3 and 4 infect an expanding host range of animal species and are zoonotic to humans. Historical animal models include various species of nonhuman primates, which have been indispensable for the discovery of human HEV and for understanding its pathogenesis and course of infection. With the genetic identification and characterization of animal strains of HEV, a number of naturally occurring animal models such as swine, chicken, and rabbit have recently been developed for various aspects of HEV research, including vaccine trials, pathogenicity, cross-species infection, mechanism of virus replication, and molecular biology studies. Unfortunately, the current available animal models for HEV are still inadequate for certain aspects of HEV research. For instance, an animal model is still lacking to study the underlying mechanism of severe and fulminant hepatitis E during pregnancy. Also, an animal model that can mimic chronic HEV infection is critically needed to study the mechanism leading to chronicity in immunocompromised individuals. Genetic identification of additional novel animal strains of HEV may lead to the development of better naturally occurring animal models for HEV. This article reviews the current understanding of animal models of HEV infection in both natural and experimental infection settings and identifies key research needs and limitations.